2020
DOI: 10.1002/jcp.29611
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐802 accelerates hepatocellular carcinoma growth by targeting RUNX3

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide. Prognosis is often unfavorable. In this study, the effects of microRNA-802 (miR-802) on HCC progression were assessed in vivo and in vitro. miR-802 was found to be significantly upregulated in HCC tumor tissue compared to paired adjacent nontumor tissue. In vitro, transfection with a miR-802 mimic accelerated SMMC-7721 cellular proliferation, increased accumulation of the cell-cycle S-phase cell populations, as well as cell migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Moreover, miR-802 overexpression significantly inhibited while miR-802 knockdown promoted ZNF521 mRNA and protein in HCC cells ( P < 0.05, Figure 6 C-D). In HCC tissues, our results showed that miR-802 was up-regulated in HCC tissues compared to adjacent non-tumor tissues ( P < 0.05, Figure 6 E), which was consistent with previous studies 20 . We also confirmed an inverse correlation between ZNF521 mRNA and miR-802 in HCC tissues ( r =-0.7223, P < 0.05, Figure 6 F).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, miR-802 overexpression significantly inhibited while miR-802 knockdown promoted ZNF521 mRNA and protein in HCC cells ( P < 0.05, Figure 6 C-D). In HCC tissues, our results showed that miR-802 was up-regulated in HCC tissues compared to adjacent non-tumor tissues ( P < 0.05, Figure 6 E), which was consistent with previous studies 20 . We also confirmed an inverse correlation between ZNF521 mRNA and miR-802 in HCC tissues ( r =-0.7223, P < 0.05, Figure 6 F).…”
Section: Resultssupporting
confidence: 92%
“…miR-802 negatively regulated the expression of ZNF521 mRNA and protein in HCC cells. Previous studies reported that miR-802 accelerates hepatocellular carcinoma growth by targeting Runx3 [20]. High blood miR-802 is associated with poor prognosis in HCC patients by regulating DNA damage response 1 (REDD1)mediated function of T cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al [68] demonstrated miR-802's ability to inhibit the aggressive behaviors of non-small cell lung cancer cells. However, it has also been described that miR-802 can accelerate the growth of hepatocellular carcinoma (HCC) [69] and that its high concentration in blood is associated with a poor prognosis in HCC patients [70]. Furthermore, miR-802 has been shown to partake in obesity-induced nephropathy in obese human and mice [71].…”
Section: Mir-802mentioning
confidence: 99%
“…MiR-802 possesses multiple function. It has been reported to regulate cancer development, alleviate lipopolysaccharide (LPS)-induced acute lung injury, and modulate the expression of human angiotensin II type I receptor [38][39][40]. In the term of metabolism, miR-802 impairs glucose metabolism and causes nephropathy in both obese mice and human [41,42].…”
Section: Discussionmentioning
confidence: 99%